Penyuluhan Hukum Tentang Penghapusan Kekerasan Dalam Rumah Tangga Di Desa Lipu Mangau Kab. Buton Selatan - rizki mustika suhartono; Ernawati; L.M. Ricard Zeldi Putra; Eko Satria; Nanda Prastika; Hayatul Jannah Ar-Rayyan; La Gurusi (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
This legal counselling activity is carried out to provide understanding to the community. This legal counselling is carried out based on the phenomenon that still occurs regarding domestic violence. Domestic Violence (KDRT) is one of Indonesia's most common forms of gender-based violence. The rise of domestic violence (KDRT) cases is a serious problem that cannot be underestimated. The PKDRT Law / Elimination of Domestic Violence is a guarantee given by the state to prevent domestic violence, take action against perpetrators, and protect victims. The method used is participatory, which is expected to play an active role in this legal counselling activity in the form of socialisation regarding the elimination of domestic violence regulated by law number 23 of 2004 concerning the elimination of domestic violence in articles 44 to 49.